The impact of India’s onion policy on local growers and communities - Ashutosh Sharma (Journal of Agriculture, Food Systems, and Community Development)
India’s recurring onion price crises exemplify the intersection of structural agricultural inefficiencies, speculative market practices, and flawed policy interventions. This viewpoint investigates the causes of extreme price swings in India’s onion markets, focusing on systemic vulnerabilities such as hoarding, infrastructure deficits, and inconsistent governance. Drawing on empirical data from government reports, agricultural studies, and market analyses, we argue that speculative trading and political collusion exacerbate natural supply-demand imbalances, disproportionately harming smallholder farmers and consumers. By prioritizing decentralized solutions like blockchain-enabled farmer cooperatives and solar-powered micro-storage, this viewpoint demonstrates how empowering local communities can result in retaining profits within rural economies and fostering climate-resilient agricultural systems. These strategies align with circular economy principles and address intergenerational equity by curbing the migration of youth out of farming regions.